Cancer-Related Intrusive Thoughts Predict Behavioral Symptoms Following Breast Cancer Treatment - Dupont, Alexandra (2013)
OBJECTIVE: Behavioral symptoms are common in breast cancer survivors, including disturbances in energy, sleep, and mood, though few risk factors for these negative outcomes have been identified. Our study examined intrusive thoughts as a predictor of lingering symptoms in breast cancer survivors in the year following treatment. METHOD: Data come from the Moving Beyond Cancer psychoeducational intervention trial, aimed at easing the transition from patient to survivor. Women (n = 558) completed psychosocial questionnaires within 4 weeks posttreatment and again 2, 6, and 12 months later. We examined intrusive thoughts about cancer at the baseline assessment as a predictor of fatigue, sleep problems, pain, breast cancer-specific symptoms, depressive symptoms, negative affect, and quality of life using growth curve modeling, controlling for study condition and other covariates. RESULTS: Intrusive thoughts were associated with higher levels of all symptoms at baseline and at the 12-month assessment. Intrusive thoughts also influenced the trajectory of pain, depressive symptoms, negative affect, and physical functioning over time; women with higher intrusions at baseline started worse and improved over time, whereas those with lower intrusions remained at a constant, lower level over time. Intrusions were not associated with the trajectory of fatigue, sleep, breast cancer-specific symptoms, or mental functioning; women with higher intrusions at baseline started worse and remained worse over time. CONCLUSION: Intrusive thoughts are associated with enduring elevations in behavioral symptoms and impaired quality of life in the year after breast cancer treatment and may be a risk factor for poor outcomes.